Expressão gênica endometrial de -inibina e betaglicano e falha de implantação em mulheres submetidas a fertilização in vitro - Camila Oliveira da Silveira (2015)
Embryo implantation involves a complex sequence of events, and a large amount of molecules have been postulated to be involved in the interaction of embryo and endometrium. This study evaluated the endometrial expression of -inhibin and betaglycan in the mid-secretory phase of women scheduled to IVF and tested whether these markers are associated with implantation failure. We conducted a nested case-control study including 52 women submitted to in vitro fertilization (IVF) and embryo transfer, divided into two groups: cases with implantation failure (n=33) and controls with confirmed clinical pregnancy (n=19). Endometrial -inhibin and betaglycan gene expression was evaluated in the mid-secretory phase of the natural menstrual cycle immediately before IVF, using real time PCR. We found a higher gene expression of -inhibin and betaglycan in implantation failure patients compared to confirmed clinical pregnancy patients. The areas under receiver operating characteristics curves for prediction of implantation failure in this context were, respectively, 0.692 and 0.678 for -inhibin and betaglycan. The present results suggest that high expression levels of -inhibin and betaglycan transcripts in secretory phase endometrium may associated to a implantation failure in IVF treatment.